Does the fall in crude oil prices really affect the Malaysian ringgit? - Amirullah, Muhammad Adli; Hamid, Zarinah (Springer International Publishing, 2018)
The sudden drop in Malaysia exchange rate triggers a big question mark and of great concern to policy makers, investors, firms and Malaysian public at large. Theoretically, depreciation in any currency is not only caused by classical exchange rate determinant but various forces behind it. This study uses monetary approach to test the Malaysia exchange rate determinant. It also seeks to examine the correlation of Malaysia exchange rate with crude oil price. The sudden drop in the global crude oil price is one of the major factors of depreciation in the Malaysian Ringgit as claimed by some analysts. Using monthly data from January 2006 to March 2016 in the first regression, we adopted the monetary approach on exchange rate determinant without crude oil price variable and found that approximately 51% of the proposition of variation of the dependent variable is explained by the proposition of variation of the independent variables. When another explanatory variable, i.e. Brent Crude Oil prices is added to the model, the results indicated that this variable is very significant and caused R2 to increase tremendously to 91%. The model is further enhanced by remedying the multicollinearity problem and omitting one of the variables which has a high correlation with all other variables. In conclusion, the fall in crude oil prices does affect the Malaysia exchange rate heavily. The finding is useful to the policy makers to devise a policy in future which is less reliant on crude oil price.